Can entrepreneurship be learned? Investigating the mediating effects of entrepreneurial competencies and mindset on the relationship between entrepreneurial education and intention - Caras, Je-ann Mae Garbosa (Animo Repository, 2022)
As the interest of the Filipino youth in entrepreneurship continues to grow, the role of education has been emphasized in the development of the competencies and mindset needed to pursue this field. In the fulfillment of the K to 12 Program, entrepreneurship serves as one of the promising features which the governing bodies in the education sector seek to highlight and attain. Accordingly, this study aims to determine how Entrepreneurial Competencies (EC) and Entrepreneurial Mindset (EM) mediate the relationship between Entrepreneurial Education (EE) and Entrepreneurial Intention (EI) as seen in the Grade 12 Accountancy, Business, and Management Senior High School students in Metro Manila. This study is a mixed-method research wherein the quantitative data were obtained through online survey questionnaires administered to 425 respondents. Whereas, the qualitative data were collected through online interviews of 31 participants. Likewise, this study follows Baron and Kenny’s method and mediation analysis and path analysis using R for the quantitative analysis; meanwhile, thematic analysis was used for the qualitative analysis. Through pattern matching, it was reported that the relationship of the variables within this model was supported by the results of the questionnaires and interviews. Hence, the results showed that the students demonstrated a high level of EI, EC, and EM, with their EE being deemed effective. Moreover, students with EE have a tendency to develop an intention to start a business. In nurturing this EI, the EE of the students similarly fosters their competencies and mindset needed to become an entrepreneur. As such, the results suggest that EC and EM mediate the relationship between EE and EI. Overall, the students’ education, knowledge or experience in business and entrepreneurship serves as a significant factor in acquiring the essential competencies and mindset that would help develop their intention to put up a business venture.